The Impact of a Classroom Intervention on Grade 10 Students' Argumentation Skills, Informal Reasoning, and Conceptual Understanding of Science - Venville, G.; Dawson, Vaille (John Wiley & Sons, Inc., 2010)
The literature provides confounding information with regard to questions about whether students in high school can engage in meaningful argumentation about socio-scientific issues and whether this process improves their conceptual understanding of science. The purpose of this research was to explore the impact of classroom-based argumentation on high school students' argumentation skills, informal reasoning, and conceptual understanding of genetics. The research was conducted as a case study in one school with an embedded quasi-experimental design with two Grade 10 classes (n = 46) forming the argumentation group and two Grade 10 classes (n = 46) forming the comparison group. The teacher of the argumentation group participated in professional learning and explicitly taught argumentation skills to the students in his classes during one, 50-minute lesson and involved them in whole-class argumentation about socio-scientific issues in a further two lessons. Data were generated through a detailed, written pre- and post-instruction student survey.The findings showed that the argumentation group, but not the comparison group, improved significantly in the complexity and quality of their arguments and gave more explanations showing rational informal reasoning. Both groups improved significantly in their genetics understanding, but the improvement of the argumentation group was significantly better than the comparison group. The importance of the findings are that after only a short intervention of three lessons, improvements in the structure and complexity of students' arguments, the degree of rational informal reasoning, and students' conceptual understanding of science can occur.